Evaluation of knowledge, attitude, and practice of medical and dental postgraduates toward reporting of adverse drug reactions in a teaching hospital, South India - Gottipati Naga Haritha, Annamalai Rama, Anup Naha, Usha Rani (Journal of Applied Pharmaceutical Science, 2022)
This study aims to assess medical and dental postgraduates’ knowledge, attitude, and practice (KAP) toward reporting adverse drug reactions (ADRs) and compare the KAP between the medical and dental postgraduates. A cross-sectional questionnaire-based study was conducted on 208 postgraduates (medical and dental postgraduates combined). The medical postgraduates belong to a tertiary care teaching hospital that is 2,000 bedded, serving a population of 1,177,361 in the southwest part of Karnataka, whereas the Dental postgraduates belong to teaching Dental hospitals from the same region as the above hospital received their accreditation by the Dental Council of India in 1970. Both the postgraduates had low KAP about the reporting system of ADRs and the ADR reporting system situated in this hospital. This study also found that the majority of the postgraduates had not attended the training sessions regarding the reporting of ADRs. This study concludes that the ADR reporting is crucial for all healthcare providers so that it initiates the exact actions by healthcare providers through which adverse events can be prevented, and will help in better drug management and thus the reputation of the hospital can be upgraded.
Keywords: Pharmacovigilance, adverse drug reactions, pharmaceuticals, healthcare professionals